Investigating the cultural component in EFL textbooks: texts and illustrations - Dana Shayakhmetova, Elmira Gerfanova, Tanat Ayapova, (Opción, 2019)
The article analyzes the cultural component in three prominent English as a foreign language (EFL) textbooks which are employed in the language programmes of higher school of Kazakhstan via intercultural communicative approach as a method. The findings indicate that the textbooks contain primarily topics of surface culture and omit invisible forms of culture which are crucial for understanding the target language culture. In conclusion, in Kazakhstani FL educational context there has risen an urgent need for developing EFL textbooks which will be oriented not only to the target and international culture but students’ native culture as well